Keanekaragaman Kultivar Salak Pondoh di Banjarnegara - Annisaurrohmah Annisaurrohmah; Wiwik Herawati; Pudji Widodo (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
Snake fruit (Salacca zalacca (Gaertner) Voss) is originated from Indonesia. The aim of this study was to find out the cultivar diversity of salak pondoh in Banjarnegara, and to determine the similarity relatiinshipa between cultivars pondoh in Banjarnegara. The method used was exploratory survey with purposive random sampling. Morphological characteristics observed included 50 characters in the form of stems, leaves, flowers, fruits, seeds, and spines. Samples were taken at 5 districts namely Madukara, Banjarmangu, Sigaluh, Pagentan and Banjarnegara. The result of this research showed that there were six cultivars of Salacca zalacca namely cultivars ‘Pondoh Nglumut’, ‘Linting’, ‘Ketek’, ‘Manggala’, ‘Madu’, and ‘Super’. Whereas in S. zalacca 'Pondoh Ketek' has various number of seeds in the fruit. The most closely related cultivars were ‘Pondoh Nglumut’ and ‘Super’. The most distinct cultivars were S. zalacca ‘Manggala’ and ‘Ketek’.